Synthesis and Physical and Thermodynamic Properties of Lactic Acid and Malic Acid-Based Natural Deep Eutectic Solvents - Castro, Vânia I. B. (2019)
The research leading to these results has received funding provided by Fundacio para a Ciencia e a Tecnologia through the project PTDC/BBB-EBB/1676/2014-DesZyme. Funding from the European Union, Horizon 2020 program has also been granted through project Des.solve (ERC consolidator) ERC-2016-COG 725034. This work was supported by the Associate Laboratory for Green Chemistry, LAQV, which is financed by national funds from FCT/MCTES (UID/QUI/50006/2013) and cofinanced by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007265).